DEVELOPMENT OF APPROACHES TO BUILDING A SYSTEM FOR ASSESSING THE PERSONNEL POTENTIAL OF THE ENTERPRISE - POSVALIUK, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The main approaches to building an effective system for assessing the personnel potential of an enterprise have been studied. Emphasis is placed on the importance of evaluating human resources as a key factor in ensuring the competitiveness and sustainable development of the organization. The necessity of adapting assessment methods to the conditions of the modern labor market and the requirements arising from technological and organizational transformations has been explored. Based on the analysis of existing practices, recommendations are provided for improving the system of assessing personnel potential in a dynamic business environment.In the current conditions of rapid economic changes, technological innovations, and the globalization of the labor market, effective management of the personnel potential of an enterprise has become one of the most important components of its competitiveness and long-term success. Therefore, the successful functioning of an organization largely depends on how effectively human resources are utilized, what skills and competencies employees need to achieve the enterprise’s strategic goals, as well as how their continuous improvement is organized. One of the main issues is the insufficient attention to formalizing and optimizing the processes of assessing personnel potential, which leads to uncertainty in identifying the strengths and weaknesses of staff, as well as to ineffective personnel development planning. Existing assessment methods often fail to meet current requirements: they are outdated, do not take into account the specifics of the enterprise and its goals, and are also unable to objectively assess the real potential of employees, considering the new demands for their professional level. There is a significant gap between theoretical developments and practical approaches to personnel potential assessment, which complicates the process of making sound management decisions in the areas of recruitment, evaluation, and development of personnel.
Keywords: personnel; personnel potential; evaluation system; personnel management; evaluation tools